Design and behaviour of the Large Hadron Collider external beam dumps capable of receiving 539 MJ/dump. (16th November 2021) - Maestre, J.; Torregrosa, C.; Kershaw, K.; Bracco, C.; Coiffet, T.; Ferrari, M.; Franqueira Ximenes, R.; Gilardoni, S.; Grenier, D.; Lechner, A.; Maire, V.; Martin Ruiz, J.M.; et al.
Abstract: Two 6 t beam dumps, made of a graphite core encapsulated in a stainless steel vessel, are used to absorb the energy of the two Large Hadron Collider (LHC) intense proton beams during operation of the accelerator. Operational issues started to appear in 2015 during LHC Run 2 (2014–2018) as a consequence of the progressive increase of the LHC beam kinetic energy, necessitating technical interventions in the highly radioactive areas around the dumps. Nitrogen gas leaks appeared after highly energetic beam impacts and instrumentation measurements indicated an initially unforeseen movement of the dumps. A computer modelling analysis campaign was launched to understand the origin of these issues, including both Monte Carlo simulations to model the proton beam interaction as well as advanced thermo-mechanical analyses. The main ﬁndings were that the amount of instantaneous energy deposited in the dump vessel leads to a strong dynamic response of the whole dump and high accelerations (above 200 g). Based on these ﬁndings, an upgraded design, including a new support system and beam windows, was implemented to ensure the dumps' compatibility with the more intense beams foreseen during LHC Run 3 (2022–2025) of 539 MJ per beam. In this paper an integral overview of the operational behaviour of the dumps and the upgraded configurations are discussed.